"Shummun, Bukmun, 'Umyun", Words in Ayat Quranic: A Stylistic Analysis to Understand Language Nuances and Deep Meanings - Ashief el Qorny; Rifqi Aulia Rahman; Ahmad Rois; Erlinda Tria Kardini (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
The Ayat of the Quran contains a wealth of meanings and deep nuances of language. In this study, we conducted a stylistic analysis of the words صمّ، بكم، عمي in Quranic Ayats to explore deeper nuances of language and meaning. This method of analysis involves tracing the use of these keywords in various ayat contexts and research related to the grammar and semantics of the Quran. The results showed that the words are often used in contexts emphasising the importance of listening, observing, and understanding the divine message. They also give a new dimension to understanding blindness and deafness in a spiritual context. This research provides further insight into the use of language in the Quran, illustrating how certain words evoke feelings, reflection, and deep appreciation of religious teachings. By stylistically analysing, this research contributes to a further understanding the use of Arabic in religious literature and bridges the gap between classical texts and contemporary understanding